The enemies of leadership : - Bogue, E Grady (Phi Delta Kappa Educational Foundation, 1985)
School principals will look in vain for five easy steps to good relationships with parents. Yet, this is an eminently practical book, a handbook for survival as well as excellence in leadership and sleeping with a clear conscience